2019
DOI: 10.1186/s13019-019-1031-7
|View full text |Cite
|
Sign up to set email alerts
|

Repair of a type B aortic dissection with a re-vascularization of the aberrant right subclavian artery in an adult patient

Abstract: BackgroundAn aberrant right subclavian artery which arises from the proximal descending aorta may result in aortic dissection. The dissection may occur at either the site of the primary intimal tear or from an aortic branch. These conditions may lead to blood flow limitation and possible aneurysmal degeneration in the future.Case presentationWe described the clinical presentation and management of a 54-year old patient diagnosed with a rare case of an aberrant right subclavian artery with Stanford Type B aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The final review included eight relevant case series 4 5 6 7 8 9 10 11 and 24 single case reports 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 comprising a total of 85 patients ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The final review included eight relevant case series 4 5 6 7 8 9 10 11 and 24 single case reports 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 comprising a total of 85 patients ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some rare cases, patients may present with compressive symptoms on the trachea and esophagus. They will usually have dysphagia of solid food [8] .…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed previous cases with one or more anomalies (Table 1). 2,720 Nonami et al. 7 reported that a patient with ARSA and ILVA with aortic aneurysm successfully underwent aortic arch replacement with five branches, in 1998.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional TEVAR is unsuitable for all patients because of landing zone limitations. Other surgeons have reported aortic dissection or aneurysm with ARSA or ILVA occurring alone, treated with total endovascular repair, 912 hybrid procedure, 1217 or open surgery. 1820…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation